INVESTIGATING THE STUDENTS' WORK IN TRANSLATING RECOUNT TEXT FROM INDONESIA TO ENGLISH THROUGH GOOGLE FORM: MORPHOLOGICAL ERRORS - Irawansyah, Irawansyah (STKIP Persada Khatulistiwa Sintang, 2024)
The objective of this study is to determine what morphological errors appear in students' sheet translations of recount texts from Indonesian to English by using surface strategy taxonomy (SST). SST is classified into omission, addition, Misformation and misordering. Descriptive qualitative research was performed in this study. 15 college students from a variety of major backgrounds were randomly selected for the sample by sharing a Google form. Testing and documenting were the research instruments employed in this investigation. The results of this study demonstrate that students made 130 morphological errors when translating recount text. The most common morphological error is an inflectional error which appears 37 times while the least common is a pronoun error and auxiliary error which appears 6 times. Meanwhile, the errors that frequently occur in surface strategy taxonomy are Misformation error which appears 58 times, followed by omission error 42 times and addition error 30 times. In this study, resarcher did not find any misordering errors that appeared. Keywords: Error Analysis, Morphological Error, Recount Text, Surface Strategy Taxonomy, Translation